Al-Būṭī vs. Al-Qaraḍāwī: A Comparative Study of Thought on Al-Khurūj 'Alā Al-Ḥukkām - Harun, Muhammad Safwan; Abdullah, Luqman; Ali, Abdul Karim; Rosele, Muhammad Ikhlas; Nor Mohd Zulkarnain, Saiful Islam; Syed Jaafar, Syed Mohd Jeffri (Mazahib, 2025)
This study examines the polemic of al-khurūj ‘alā al-ḥukkām (rebellion against rulers) as debated by Yūsuf al-Qaraḍāwī and Muḥammad Sa‘īd Ramaḍān al-Būṭī, particularly in the context of the Syria crisis and the Arab Spring. The theoretical framework employed is maqāṣid al-sharīʿah, encompassing the hierarchy of maṣlaḥah based on ḍarūriyyāt, ḥājiyyāt, and taḥsīniyyāt; the preservation of the kulliyyāt al-khams (religion, life, intellect, lineage, and property); the balancing of conflicting mafsadah; the application of sadd al-dharāʾiʿ (blocking the means to harm); and the consideration of maʾālāt (future consequences). Methodologically, the study employs a qualitative textual analysis of fatwa, jurisprudential writings, and theological arguments by scholars, situating their views within the broader maqāṣid framework. Within this framework, al-Qaraḍāwī justifies rebellion against unjust rulers as both a moral duty and a religious obligation to uphold justice, framing it within the maqāṣid imperative of resisting tyranny. Conversely, al-Būṭī employs the same maqāṣid tools to prohibit rebellion, prioritising the avoidance of bloodshed and societal collapse over immediate political reform. The findings reveal that although both scholars engage maqāṣid al-sharīʿah, their divergent prioritisation leads al-Qaraḍāwī to emphasise justice and activism as central to preserving Islam’s dignity. At the same time, al-Būṭī underscores stability and unity as essential safeguards against greater chaos.